Implementasi Audit Manajemen Sumber Daya Manusia dalam Memotivasi Kinerja Karyawan di CV Cipta Alignment Construction - Ahmad Qolbi Salim; Made Dudy Satyawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of human resource management (HRM) audits in motivating employee performance at CV Cipta Alignment Constructions (CV.CLC). HRM audits serve as an evaluative and strategic tool in assessing the effectiveness of personnel functions such as recruitment, training, career development, and reward systems. The study used a qualitative approach with a case study method through interviews, observation, and documentation. The results show that HRM audits have a positive effect on employee motivation and performance by increasing work morale, placing employees according to competencies, and reducing turnover. Based on Resource-Based Theory (Barney, 1991), HRM audits are valuable and difficult-to-imitate strategic resources, thus supporting a company's competitive advantage. These findings emphasize the importance of implementing HRM audits continuously as part of a management strategy to improve organizational effectiveness. The implications of this study provide recommendations for companies to integrate HRM audits into strategic planning to achieve optimal and sustainable performance. In addition, this study also opens opportunities for further studies to strengthen the implementation of HRM audits in different sectors and company scales.